Subethnische dimensionen des veraenderungsmanagements in asiatischen klein- und mittelunternehmen: Trends in Singapur - Badibanga, Ulrike (Institutional Knowledge at Singapore Management University, 2005)
Against the background of a rapidly changing business environment, the article examines the organisational change management behavior of the owner-managers of small and medium-sized enterprises in Singapore. The analysis of survey data is aimed at ascertain whether there are any differences between Chinese and English-educated small (Chinese) businessmen in terms of Change Management (CM), a dichotomy which is of great historical and politico-cultural significance in Singapore. The survey data show that there are indeed differences between the subgroups (e.g. with regard to the initiation of a more participatory people management style) but these variations turned out to be far less pronounced than expected. Access to information appears to be a key antecedent of the various change management approaches used by both groups. Chinese-educated businessmen in particular seem to be somewhat disadvantaged in this respect as the modern management literature is largely published in English.